Depression: a challenge in general medical practice - Giacomantone, Eduardo G. (Revista del Hospital Italiano de Buenos Aires, 2019)
Associated or not with an organic disease, depression has a high prevalence in medical practice but is underdiagnosed. The mood disorder usually coexists with varied somatic complaints and chronic pain, forming mixed syndromes with a complex differential diagnosis. This article describes different clinical presentations of depression in general medicine, with emphasis on atypical depressive states, masked depressions very relevant for their frequency and consequences: post-surgical depression, chronic painful conditions such as headaches or lumbago, chronic fatigue and fibromyalgia. Only the recognition and diagnosis of the underlying depression will enable the implementation of appropriate therapeutic interventions. Some recommendations for the use of antidepressant drugs in primary care and the eventual psychiatric consultation are also reviewed
Keywords: depression; general medical practice; chronic pains; fibromyalgia; fatigue; masked depression